Valores éticos de la responsabilidad social interna en centros de producción audiovisual (2014)
This article is concerning the theorizing of the main aspects of ethical, social and moral values, as part of social responsibility in audiovisual production centers, in private universities. Since the primary objective was “to identify the ethical values of the internal Social Responsibility in Audiovisual Production Centers of private universities”. It was necessary to apply a descriptive research design and not experimental, on transversal field, so that the variable was not manipulated. Its population was comprised of 14 people, who underwent an instrument of questionnaire type, which was subjected to a process of validity, through the criterion of five experts. According to the analysis of the results, it was shown that 49% of people are actually identified as the layout object. In the conclusions, as in the analysis, it was observed that the highest percentage of respondents respect the rules of work, there is equal treatment without discrimination of staff and they are willing to accept the possibility of job changes by promotion. Because of this, the researchers made certain recommendations, which indicate that it is important to have assessments and activities that encourage the ethical, or the importance and professional well-being, as well as facilitate training courses.